Arabic Neologisms in Indonesian and Malaysian Arabic Media - Uki Sukiman; Ghazali Zainuddin; Yoyo Yoyo; Siti Rosilawati Ramlan (Al-Jami'ah Research Centre, 2024)
Al-Jami'ah Journal of Islamic Studies Vol 61, No (page: 365-392)